Dusting off the Perception of Risk and Returns in FOREX Markets - Phornchanok Cumperayot (Center for Economic Studies and ifo Institute (CESifo), 2003)
In this paper, we construct alternative theoretical models for exchange rates by introducing additional risk factors, based on the volatility of macroeconomic fundamentals. The modified flexible-price monetary model is used to characterize the long-run equilibrium of exchange rates, while the modified sticky-price model explains the adjustment towards the long run. Empirically, in a number of OECD countries we find cointegration relationships between the exchange rate and macroeconomic variables and also some evidence for the long-run equilibrium error correction. Macroeconomic uncertainty can significantly explain the variation of the exchange rate from its fundamental-based value. The results lead us to believe that macroeconomic sources of FOREX risk may be a missing factor in the exchange rate study.
Keywords: 330; flexible-price and sluggish-price exchange rate models; expectation formations; macroeconomic risk; risk premium; asset pricing